O ZASADNOŚCI UNORMOWANIA W KODEKSIE SPÓŁEK HANDLOWYCH KONSTRUKCJI NADUŻYCIA FORMY SPÓŁKI - Frelek, Krystian (Zeszyty Prawnicze, 2016)
ON THE JUSTIFICATION OF THE NEED TO INTRODUCE INTO THE POLISH COMMERCIAL COMPANIES CODE (KSH) OF A REGULATION CONCERNING THE ABUSE OF PARTNERSHIPS AND COMMERCIAL COMPANIES Summary The aim of this article is describe what is meant by the abuse of partnerships and commercial companies and to present the merits of the proposed regulation to control the phenomenon. The author explains that the abuse of partnerships and commercial companies is a collective definition covering a variety of cases in which one or more partners or shareholders abuse the partnership or commercial company for purposes not in compliance with those intended by the law. This usually means the avoidance of legal liability by persons who are managing a partnership or commercial company. A businessman who is unable to achieve his commercial aims within the legal scope of business activities may resort to the abuse of his company. It is the legislator’s duty to curb such behaviour, which is a threat to other entities involved in commercial activities, especially as regards a company’s creditors.